Vitamin A supplementation status and associated factors among children aged 6–59 months in Tanzania: a multi-level analysis - Gebrekidan, Amanuel Yosef; Asgedom, Yordanos Sisay; Woldegeorgis, Beshada Zerfu; Kassie, Gizachew Ambaw; Haile, Kirubel Eshetu; Damtew, Solomon Abrha; Teklay, Ashenafi; Ayele, Amare Demsie (Frontiers in Nutrition, 2024)
Background: Vitamin A supplementation every four to six months is an economical, rapid, and effective strategy to enhance vitamin A status and minimize child morbidity and mortality due to vitamin A deficiency in the long run. Therefore, this study was aimed at investigating the level as well as the factors influencing VAS status among children aged 6–59 months in Tanzania. Methods: This analysis relied on data from the 2022 Tanzania Demographic and Health Survey (TDHS). The study used a weighted sample of 9382 children aged 6–59 months. Given the effect of clustering and the binary character of the outcome variable, we employed a multilevel binary logistic regression model. The adjusted odds ratio (AOR) with a 95% confidence interval (CI) was used to determine statistical significance, considering the model with the lowest deviation that best fits the data. Results: In this study, vitamin A supplementation among children aged 6–59 months was found to be 53.18% [95% CI: 52.17, 54.19]. Mother's/caregiver’s working status; Working [AOR=1.59, 95% CI: 1.34, 1.89], ANC follow-up [AOR=1.71, 95%CI: 1.34, 2.2], and health facility delivery [AOR=1.55, 95%CI: 1.25, 1.91] were individual-level factors associated with vitamin A supplementation. Whereas administrative zones of Western [AOR=2.02, 95% CI: 1.16, 3.52], Southern highlands [AOR=3.83, 95% CI: 2.02, 7.24], Southern administrative zone [AOR=2.69, 95% CI: 1.37, 5.3], and South West highlands [AOR=0.56, 95% CI: 0.33, 0.95] were community-level factors associated with vitamin A supplementation. Conclusion: The proportion of VAS among children in Tanzania is low compared to UNICEF’s target of 80. Mother's /caregiver’s working status, antenatal care, place of delivery, community-level media exposure, and administrative zones were significantly associated factors with vitamin A supplementation. Therefore, interventions should be designed to improve the uptake of VAS. Provision and promotion of ANC and institutional delivery and strengthening of routine supplementation are recommended to increase coverage of childhood vitamin A supplementation. Moreover, special focus should be given to regions in the south-western highlands.